Rapid preparation method of high-performance inorganic plastic thermoelectric material

The rapid preparation of inorganic plastic thermoelectric materials through induction heating and smelting method solves the problems of long synthesis cycle, high cost and mechanical properties in traditional methods, and achieves high-performance and low-cost rapid preparation and large-scale production.

CN119663041APending Publication Date: 2025-03-21HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411839409.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing synthesis methods of inorganic plastic thermoelectric materials have problems such as difficulty in achieving precise proportion control, long synthesis cycles, high costs and possible impact on mechanical properties.

Method used

Using a rapid preparation method based on induction heating, by induction heating and smelting in vacuum-sealed quartz tubes, the rapid preparation of inorganic plastic thermoelectric materials can be achieved by only 1000℃-1100℃ for 10-20 minutes.

Benefits of technology

It realizes the rapid preparation of inorganic plastic thermoelectric materials, which is simple to operate, short to use and low cost, and the material has high performance characteristics in terms of thermoelectric properties and plasticity, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663041A_ABST
    Figure CN119663041A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of thermoelectric materials, and discloses a rapid preparation method of a high-performance inorganic plastic thermoelectric material, which comprises the following steps: (1) weighing elementary substance material powder corresponding to each element according to the nominal chemical dosage ratio of each element in the chemical formula of the inorganic plastic thermoelectric material; (2) mixing to obtain mixed powder; (3) putting the mixed powder into a quartz tube, vacuumizing and sealing; and (4) placing the vacuum-sealed quartz tube in a graphite crucible, then placing the crucible in an induction heating coil, heating to 1000-1100 DEG C, and carrying out heat preservation for 10-20 minutes to carry out induction heating smelting so as to obtain the inorganic plastic thermoelectric material cast ingot. According to the invention, the process of the preparation method is improved, based on induction heating, the rapid preparation of the inorganic plastic thermoelectric material can be realized only by utilizing induction heating to keep the temperature at 1000-1100 DEG C for 10-20 minutes, and the prepared inorganic plastic thermoelectric material has the characteristic of high performance in the aspects of thermoelectric performance and plasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of thermoelectric materials, and more specifically, relates to a method for rapidly preparing high-performance inorganic plastic thermoelectric materials. Based on induction heating, the inorganic plastic thermoelectric materials can be rapidly prepared. Background Art

[0002] In order to alleviate the increasingly severe energy and environmental problems, researchers from all over the world attach great importance to the research, utilization and development of renewable and clean energy. Emerging energy conversion technologies such as photovoltaics and thermoelectrics are booming and have attracted widespread attention. Thermoelectric materials are functional materials that can realize the mutual conversion of thermal energy and electrical energy. They have important application value in the fields of temperature difference power generation, all-solid-state refrigeration, and precise temperature control. Its basic principles are: Seebeck Effect, Peltier Effect and Thomson Effect.

[0003] Compared with organic thermoelectric materials, inorganic thermoelectric materials have better carrier mobility, so their thermoelectric performance is generally better than that of organic thermoelectric materials, and the difference can reach 1 to 3 orders of magnitude. In addition to the above characteristics of inorganic thermoelectric materials, inorganic plastic thermoelectric materials also have the advantages of plasticity, show unique mechanical properties, and have broad application prospects. Common synthesis methods of inorganic thermoelectric materials (including inorganic plastic thermoelectric materials) include high-temperature melting combined with long-term annealing (annealing time is often not less than 1 day), solvent thermal synthesis, and mechanical alloying. Among them, the main disadvantage of high-temperature melting combined with long-term annealing is that it is difficult to achieve precise control of the proportion, and the synthesis cycle is long. The disadvantage of the solvent thermal synthesis method is that the synthesis cost is high and it is difficult to carry out large-scale production. In addition, some soluble anion and cation salts are expensive and difficult to obtain, and the performance of the synthetic product is also easily affected by the reaction conditions (such as pressure, temperature, time and pH). In the preparation process of mechanical alloying, it is very challenging to control parameters such as pore size, temperature and pressure to avoid runaway phenomena, and this method may weaken the mechanical properties of the material to a certain extent. Therefore, if we can explore a preparation method that is simple to operate, takes a short time, has good effects, is low-cost, and can be mass-produced, it will be of great significance for the research and development of inorganic plastic thermoelectric materials. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for rapidly preparing high-performance inorganic plastic thermoelectric materials, wherein the process of the preparation method is improved, based on induction heating, only induction heating is required to be used at 1000℃-1100℃ for 10-20 minutes for induction heating melting, and the inorganic plastic thermoelectric materials can be rapidly prepared, which is simple to operate, short in time, low in cost, and can be mass-produced. Moreover, the obtained inorganic plastic thermoelectric materials, compared with the products obtained by traditional high-temperature melting combined with long-term annealing, also show high performance in terms of thermoelectric properties and plasticity.

[0005] To achieve the above object, according to one aspect of the present invention, a method for rapidly preparing an inorganic plastic thermoelectric material based on induction heating is provided, characterized in that it comprises the following steps:

[0006] (1) for the desired inorganic plastic thermoelectric material, under a protective atmosphere, weighing the single material powder corresponding to each element according to the nominal chemical dosage ratio of each element in the chemical formula of the inorganic plastic thermoelectric material; wherein the desired inorganic plastic thermoelectric material contains a metal element;

[0007] (2) fully mixing the powders obtained in step (1) to obtain a mixed powder;

[0008] (3) Place the mixed powder obtained in step (2) in a quartz tube and evacuate the tube to a pressure not exceeding 10 -5 After supporting, seal to obtain a vacuum-sealed quartz tube;

[0009] (4) placing the vacuum-sealed quartz tube obtained in step (3) in a graphite crucible, and then placing the graphite crucible in an induction heating coil, heating to 1000° C.-1100° C. and keeping the temperature for 10-20 minutes to perform induction heating smelting, and cooling after smelting to obtain a smelted ingot, which is an inorganic plastic thermoelectric material ingot.

[0010] As a further preferred embodiment of the present invention, the preparation method further comprises the steps of:

[0011] (5) The smelted ingot obtained in step (4) is crushed into powder to obtain inorganic plastic thermoelectric material powder.

[0012] As a further preferred embodiment of the present invention, in step (4), the heating time used for heating is 2-8 minutes.

[0013] As a further preference of the present invention, in step (4), the cooling method adopted for cooling is furnace cooling, temperature-controlled cooling or natural cooling.

[0014] As a further preferred embodiment of the present invention, in step (1), the inorganic plastic thermoelectric material to be obtained is Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 .

[0015] As a further preferred embodiment of the present invention, in step (2), the total weight of the mixed powder is not less than 100 g.

[0016] As a further preference of the present invention, in step (1), the protective atmosphere is argon.

[0017] As a further preferred embodiment of the present invention, in step (5), the pulverizing is performed using an agate mortar.

[0018] According to another aspect of the present invention, an inorganic plastic thermoelectric material obtained by the above preparation method is provided.

[0019] Through the above technical scheme conceived by the present invention, compared with the prior art, the present invention introduces electromagnetic induction heating technology, so that the raw materials reach high temperature in a very short time in a vacuum-sealed quartz tube, and a smelting reaction occurs, thereby successfully preparing an inorganic plastic thermoelectric material with a thermoelectric effect. The operation is simple, the time is short, the cost is low, and large-scale mass production can be achieved. At the same time, the electromagnetic stirring effect of the alternating magnetic field can make the temperature and composition of the metal-non-metal mixed liquid uniform, which is beneficial to the uniformity of the composition of the thermoelectric material and can effectively improve the thermoelectric performance of the material.

[0020] The main disadvantages of traditional high-temperature smelting combined with long-term annealing are that the synthesis cycle is long and it is difficult to achieve precise control of the proportion. The present invention is based on electromagnetic induction heating. By fully mixing the raw materials, applying a vacuum-sealed reaction environment, and controlling the smelting temperature and time to keep warm at 1000°C-1100°C for 10-20 minutes, these technical obstacles have been successfully overcome, and the stable synthesis of high-quality inorganic plastic thermoelectric materials has been achieved. The smelted product does not need annealing treatment, and can be cooled after the smelting is completed (natural cooling or temperature-controlled cooling that further extends the cooling time can be used). The method of the present invention not only solves the defects of traditional methods, but also lays the foundation for the large-scale preparation of inorganic plastic thermoelectric materials. Taking Example 1 and Comparative Example 1 below as examples, although both are based on Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 The nominal chemical dosage of the chemical formula is the weight of each raw material powder, but the thermoelectric properties of the product of Example 1 obtained by induction heating melting of the present invention (without annealing) are significantly better than those of Comparative Example 1 (Comparative Example 1 adopts traditional high-temperature melting and is annealed); and the Ag2S prepared by the method of the present invention 1 / 3 Se 1 / 3 Te 1 / 3Compared with the Ag2S prepared by traditional high-temperature melting combined with long-term annealing reported in the prior art (such as: Chen H, Shao C, Huang S, et al. High-EntropyCubic Pseudo-Ternary Ag2(S,Se,Te)Materials With Excellent Ductility andThermoelectric Performance[J]. Advanced Energy Materials, 2024, 14(10). DOI: 10.1002 / aenm.202303473. 1 / 3Se 1 / 3 Te 1 / 3 The material exhibits better plasticity. It can be seen that the material prepared by the rapid preparation method of the inorganic plastic thermoelectric material by induction heating in the present invention has the characteristics of high performance.

[0021] The present invention adopts an electromagnetic induction heating melting method to synthesize an inorganic plastic thermoelectric material, which is simpler to operate, takes less time, has lower cost, is suitable for large-scale production, and is environmentally friendly.

[0022] The inorganic plastic thermoelectric material synthesized by the electromagnetic induction melting method of the present invention is highly crystallized and has excellent purity. The preparation method of the present invention can be applied to the preparation of n-type and p-type inorganic plastic thermoelectric materials and can be widely used in various thermoelectric devices.

[0023] In summary, the present invention uses electromagnetic induction heating to successfully produce inorganic plastic thermoelectric materials with thermoelectric effect. The preparation is convenient and efficient, and large-scale preparation (gram level to hundred-gram level) can be achieved. At the same time, the electromagnetic stirring effect of the alternating magnetic field can make the temperature and composition of the metal-non-metal mixed liquid uniform, which is beneficial to the homogenization of the composition of the thermoelectric material and can effectively improve the thermoelectric performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the device for preparing thermoelectric materials for electromagnetic induction heating.

[0025] Figure 2 Thermoelectric material Ag2S synthesized in Examples 1 to 3 1 / 3 Se 1 / 3 Te 1 / 3 X-ray diffraction pattern of the ingot powder.

[0026] Figure 3 Thermoelectric material Ag2S synthesized in Example 1 1 / 3 Se 1 / 3 Te 1 / 3 The power factor and temperature change curve.

[0027] Figure 4 Thermoelectric material Ag2S synthesized in Example 1 1 / 3 Se 1 / 3 Te 1 / 3 The compressive stress-strain curve of Figure 4 (a) corresponds to the compressive strain from 0 to 93%, Figure 4 (b) corresponds to the compressive strain from 0 to 45% (partially enlarged view).

[0028] Figure 5 Thermoelectric material Ag2S synthesized in Comparative Example 1 1 / 3 Se 1 / 3 Te 1 / 3 The power factor and temperature change curve. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The induction heating melting equipment used in the induction heating melting in the following examples is a HKG-15KW high frequency induction heating machine purchased from Hongkai Power Technology Co., Ltd., as shown in the schematic diagram. Figure 1 The box-type furnace used for high-temperature smelting in Comparative Example 1 is a SX2-9-12TP box-type electric furnace purchased from Zhuodi Instrument Equipment (Shanghai) Co., Ltd.

[0031] Example 1

[0032] Plastic Thermoelectric Material Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 The preparation method comprises the following steps:

[0033] (1) In a glove box, with argon as the protective atmosphere, weigh out the elemental silver, sulfur, selenium, and tellurium. The elemental masses are calculated according to the formula of Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 The chemical formula is weighed. The error range of the weighing balance used in this embodiment is ±0.0005g. The raw materials corresponding to these elements are all single elements. The amount of element Ag used in this embodiment is 8.5542g.

[0034] (2) The initially weighed powder was thoroughly mixed manually in a mortar for 30 minutes.

[0035] (3) Vacuum sealing. Place the fully mixed powder in a quartz tube and evacuate to 10 -5 Sealed after support.

[0036] (4) Induction heating melting. A vacuum-sealed quartz tube is placed in a graphite crucible, and then the graphite crucible is placed in an induction heating coil. After 2 minutes, it is heated to 1000°C and kept at this temperature for 10 minutes for high-temperature melting. After melting, the ingot is obtained by cooling the furnace.

[0037] (5) Ingot pulverization: The ingot obtained by high-temperature smelting was pulverized into powder using an agate mortar for 30 minutes.

[0038] Example 2

[0039] The only difference between this embodiment and embodiment 1 is that step (4) is to place the graphite crucible in an induction heating coil, heat it to 1100° C. for 3 minutes and keep it at that temperature for 20 minutes for high temperature smelting. The other steps and specific parameter conditions are the same as those in embodiment 1.

[0040] Example 3

[0041] The only difference between this embodiment and embodiment 1 is that the amount of element Ag used in step (1) is 102.4770 g. The other steps and specific parameter conditions are the same as those in embodiment 1. The total mass of the ingot powder finally obtained is 139.3295 g, reaching the hundred-gram level.

[0042] Figure 2 Ag2S prepared in Examples 1 to 3 1 / 3 Se 1 / 3 Te 1 / 3 X-ray diffraction pattern of ingot powder ( Figure 2 In the “simulated Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 The data are obtained by simulation with Diamond and GSAS software. The figure shows the Ag2S prepared in Examples 1 to 3. 1 / 3 Se 1 / 3 Te 1 / 3 The diffraction peaks of the ingot powder all match the diffraction peaks obtained by simulation, and no other impurity peaks are observed in the figure, confirming that the synthesized Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 The ingot powder has high purity. In particular, as can be seen from Example 3, the preparation method of the present invention can still maintain high purity when synthesizing 100-gram-level inorganic plastic thermoelectric materials.

[0043] Example 1 Synthesized plastic thermoelectric material Ag2S 1 / 3 Se 1 / 3 Te 1 / 3The power factor is 4.5 μW cm at 305 K. - 1 k -2 Increased to 6.8 μW cm at 485 K -1 k -2 ,like Figure 3 shown.

[0044] Example 1 Synthesized plastic thermoelectric material Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 The compressive stress-strain curve is as follows Figure 4 As shown in the figure, the material exhibits the characteristics of a highly plastic material, no fracture occurs within the test range, and the curve tends to be smooth and flat. Its maximum stress can exceed 600MPa, and it can be compressed from a cubic prism into a flat cylinder (compression strain exceeds 90%), indicating that the plastic thermoelectric material Ag2S synthesized by this preparation method is 1 / 3 Se 1 / 3 Te 1 / 3 It has extremely high plasticity, which is conducive to practical applications. The existing technology (see the journal literature: Chen H, Shao C, Huang S, et al. High-Entropy Cubic Pseudo-Ternary Ag2(S,Se,Te)Materials With Excellent Ductility and Thermoelectric Performance[J]. Advanced Energy Materials, 2024, 14(10). DOI: 10.1002 / aenm.202303473.) also reported the plastic thermoelectric material Ag2S prepared by traditional high-temperature smelting combined with long-term annealing. 1 / 3 Se 1 / 3 Te 1 / 3 (The method adopted in the document is to carry out high-temperature smelting at 1323K for 12 hours, and after smelting, cool to 823K for 72 hours, and carry out long-term annealing treatment). The compressive stress-strain curve of the prepared sample is measured, and it can be known that the yield stress is about 20MPa (see Figure 2(c) of the document for details). Figure 4 From (b) in the figure, it can be seen that the yield stress of the material is about 3 MPa. 1 / 3 Se 1 / 3 Te 1 / 3 It is easier to undergo plastic deformation and exhibits better plasticity.

[0045] Comparative Example 1

[0046] Plastic Thermoelectric Material Ag2S1 / 3 Se 1 / 3 Te 1 / 3 The preparation method comprises the following steps:

[0047] (1) In a glove box, with argon as the protective atmosphere, weigh out the elemental silver, sulfur, selenium, and tellurium. The elemental masses are calculated according to the formula of Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 Weighing by chemical formula. The error range of the weighing balance used in this example is ±0.0005g. The raw materials corresponding to these elements are all single elements. The amount of element Ag used in this comparative example is 8.5542g.

[0048] (2) The initially weighed powder was thoroughly mixed manually in a mortar for 30 minutes.

[0049] (3) Vacuum sealing. Place the fully mixed powder in a quartz tube and evacuate to 10 -5 Sealed after support.

[0050] (4) High-temperature smelting + annealing. The vacuum-sealed quartz tube is placed in a box furnace for high-temperature smelting. The smelting conditions are: slowly heating from room temperature to 1000°C over 15 hours, keeping at 1000°C for 24 hours and then slowly cooling to 550°C over 5 hours, keeping at 550°C for 24 hours and then cooling to room temperature with the furnace to obtain a smelted ingot.

[0051] (5) Ingot pulverization: The ingot obtained by high-temperature smelting was pulverized into powder using an agate mortar for 30 minutes.

[0052] Comparative Example 1: Plastic thermoelectric material Ag2S synthesized 1 / 3 Se 1 / 3 Te 1 / 3 The power factor and temperature change curve is as follows Figure 5 As shown, from 2.8 μW cm at 305 K -1 k -2 Increased to 5.1 μW cm at 485 K -1 k -2 .

[0053] contrast Figure 3 and Figure 5 It can be seen that the thermoelectric material Ag2S prepared in Example 1 1 / 3 Se 1 / 3 Te 1 / 3 The power factor within its application temperature range is significantly higher than that of thermoelectric materials prepared by traditional smelting methods. It can be seen that Example 1 obtained based on the present invention has higher electrical transport performance and has better application prospects in the field of thermoelectric materials. In addition, the implementation time based on the present invention is significantly less than that of traditional smelting, and its preparation efficiency is higher.

[0054] The above embodiments are only examples. For example, the protective atmosphere may be N2 gas or other inert gases in addition to argon gas; for another example, after smelting, in addition to furnace cooling, temperature-controlled cooling (the cooling time may be controlled to be, for example, 30 to 40 minutes) or natural cooling may be used.

[0055] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for rapid preparation of inorganic plastic thermoelectric materials based on induction heating, characterized in that: The following steps are involved: (1) for the desired inorganic plastic thermoelectric material, under a protective atmosphere, weighing the single material powder corresponding to each element according to the nominal chemical dosage ratio of each element in the chemical formula of the inorganic plastic thermoelectric material; wherein the desired inorganic plastic thermoelectric material contains a metal element; (2) fully mixing the powders obtained in step (1) to obtain a mixed powder; (3) Place the mixed powder obtained in step (2) in a quartz tube and evacuate the tube to a pressure not exceeding 10 -5 After supporting, seal to obtain a vacuum-sealed quartz tube; (4) placing the vacuum-sealed quartz tube obtained in step (3) in a graphite crucible, and then placing the graphite crucible in an induction heating coil, heating to 1000° C.-1100° C. and keeping the temperature for 10-20 minutes to perform induction heating smelting, and cooling after smelting to obtain a smelted ingot, which is an inorganic plastic thermoelectric material ingot.

2. The preparation method according to claim 1, characterized in that: The preparation method further comprises the steps of: (5) The smelted ingot obtained in step (4) is crushed into powder to obtain inorganic plastic thermoelectric material powder.

3. The preparation method according to claim 1, characterized in that: In step (4), the heating time used for heating is 2-8 minutes.

4. The preparation method according to claim 1, characterized in that: In step (4), the cooling method used is furnace cooling, temperature-controlled cooling or natural cooling.

5. The preparation method according to claim 1, characterized in that: In step (1), the desired inorganic plastic thermoelectric material is Ag2S 1 / 3 Se 1 / 3 Te 1 / 3 .

6. The preparation method according to claim 1, characterized in that: In step (2), the total weight of the mixed powder is not less than 100 g.

7. The preparation method according to claim 1, characterized in that: In step (1), the protective atmosphere is argon.

8. The preparation method according to claim 2, characterized in that: In step (5), the pulverization is specifically performed using an agate mortar.

9. An inorganic plastic thermoelectric material obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of thermoelectric material of skutterudite

    CN104498751A

  • Preparation method for Mg3Sb2-based thermoelectric material

    CN105695774A

  • Non-equilibrium MgAgSb-based thermoelectric material and preparation method thereof

    CN118291796A

  • Quick induction melting device of pyroelectric material

    CN205305156U

  • Manufacturing method of agsbte2 thermoelectric material NANO powder by rsp

    KR1020110121263A